The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s11069-015-1810-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alternative distributions of ground motion variability on results of probabilistic seismic hazard analysis

Abstract: Probabilistic seismic hazard analysis (PSHA) is a regularly applied practice that precedes the construction of important engineering structures. The Cornell-McGuire procedure is the most frequently applied method of PSHA. This paper examines the fundamental assumption of the Cornell-McGuire procedure for PSHA, namely, the log-normal distribution of the residuals of the ground motion parameters. Although the assumption of log-normality is standard, it has not been rigorously tested. Moreover, the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(23 reference statements)
2
2
0
Order By: Relevance
“…Although there is no obvious trend, all the estimates of ξ were negative, which confirms the convergence of data to the bounded Weibull extreme value distribution. Similar results were obtained by Huyse et al (2010) and Pavlenko (2015).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Although there is no obvious trend, all the estimates of ξ were negative, which confirms the convergence of data to the bounded Weibull extreme value distribution. Similar results were obtained by Huyse et al (2010) and Pavlenko (2015).…”
Section: Resultssupporting
confidence: 89%
“…Huyse et al (2010) applied the peaks over threshold method to analyse both the raw PGA data and the logarithmic residuals of PGA, and concluded that the generalised Pareto distribution (GPD), with the negative shape parameter, provided a model that was more accurate for the tail fractions of both the studied datasets. Similar results were obtained by Pavlenko (2015), who found that the GEVD was a more appropriate model for logarithmic residuals of PGA.…”
Section: Introductionsupporting
confidence: 88%
“…Some tests, such as the LLH test, rely on this assumption. However, the assumption of lognormally distributed residuals has become a de-facto standard and, as a result, usually is not tested routinely for new datasets, but is accepted as a given (Pavlenko, 2015;Raschke, 2013).…”
Section: Advantages and Disadvantages Of The Proposed Metricmentioning
confidence: 99%
“…The variance of the random component is equal to the residual variance of the regression analysis. However, arguments have been presented against the assumption of the log-normal distribution for the individual random component ε a (Dupuis and Flemming, 2006;Raschke, 2013a;Pavlenko, 2015). Furthermore, the residual variance is not an appropriate estimator for V(ε) because of the principal of area equivalence, as was revealed by Raschke (2013a).…”
Section: Introductionmentioning
confidence: 99%